(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2025)
This article explores the dynamics of cross-border e-commerce and its significant impact on global trade, supply chains, and the international economy. As the digital marketplace continues to evolve, businesses are increasingly engaging in international online trade, offering both opportunities and challenges. This study examines how cross-border e-commerce is reshaping supply chains, expanding global market access, and fostering innovation. Additionally, it highlights key issues in payment processing, taxation, and legal barriers that businesses face in cross-border transactions. The article concludes with an analysis of potential solutions and strategies for overcoming these challenges to optimize global e-commerce operations.